Advice to use topical or oral ibuprofen for chronic knee pain in older people: randomised controlled trial and patient preference study. Issue 7636 (4th December 2007) - Underwood, Martin; Ashby, Deborah; Cross, Pamela; Hennessy, Enid; Letley, Louise; Martin, Jeannett; Mt-Isa, Shahrul; Parsons, Suzanne; Vickers, Madge; Whyte, Ken
Abstract : Objective To determine whether older patients with chronic knee pain should be advised to use topical or oral non-steroidal anti-inflammatory drugs (NSAIDs). Design Randomised controlled trial and patient preference study. Setting 26 general practices. Participants People aged ≥50 with knee pain: 282 in randomised trial and 303 in preference study. Interventions Advice to use topical or oral ibuprofen. Primary outcome measures WOMAC (Western Ontario and McMaster Universities) osteoarthritis index, major and minor adverse effects. Results Changes in global WOMAC scores at 12 months were equivalent. In the randomised trial the difference (topical minus oral) was two points (95% confidence interval −2 to 6); in the preference study, it was one point (−4 to 6). There were no differences in major adverse effects in the trial or study. The only significant differences in secondary outcomes were in the randomised trial. The oral group had more respiratory adverse effects (17% v 7%, 95% confidence interval for difference −17% to −2%), the change in serum creatinine was 3.7 mmol/l less favourable (0.9 µmol/l to 6.5 µmol/l); and more participants changed treatments because of adverse effects (16% v 1%, −16% to −5%). In the topical group more participants had chronic pain grade III or IV at three months, and more participants changed treatment because of ineffectiveness. Conclusions Advice to use oral or topical preparations has an equivalent effect on knee pain over one year, and there are more minor side effects with oral NSAIDs. Topical NSAIDs may be a useful alternative to oral NSAIDs. Trial registration ISRCTN 79353052.